Evaluation of groundwater quality of Khorramabad plain - Siros Tahmasian; Zabihollah Khani Temeliyeh; Javad Behmanesh (محیط زیست و مهندسی آب, 2018)
Groundwater along with the path of its movement, is affected by various factors, such as the surrounding environment. Hence, the substance is introduced in the form of salts, parasite, microbes or various impurities, which causes changes to the quality and pollution of water. Therefore, the research in this regard is necessary for determining the factors affecting water quality in terms of determining the qualitative characteristics of water for different uses. In this research, a wide range of groundwater sources in Khorramabad city have been sampled and the qualitative properties of the water samples measured were ionic strength of hydrogen (pH), EC, soluble calcium, magnesium, sodium, potassium, and soluble anions of chlorine, sulfate, bicarbonate, phosphate, nitrate, and the sodium adsorption ratio, and heavy metals of cadmium and arsenic. Later, the distribution map of each parameter was mapped. The results showed that the concentration of most investigated parameters from the heights towards the southwest of Khorramabad regions were increased with the watershed output of the city. The investigated parameters were in the appropriate quality range, and among the parameters, the nitrate average concentration was 13.69 mg/l (the minimum and maximum were 1.52 and 49.55 mg/l respectively) in the Southern Khorramabad regions. In general, 50% of total groundwater quality data had the nitrate concentration over 11.2 mg/l and 10% had the concentration over 24/0 mg/L, while the standard rate is 45 mg/l.